How to write essays a step-by-step guide for all levels, with sample essays - Shiach, Don (Viva Books Private Limited, 2014)
Essay writing skills are an essential component of being a successful student at all levels. The advice and practical guidance you receive in this book will enable you to improve your grade assessments by putting into practice some simple, but invaluable principles of essay writing. These approaches will work for you whether you are facing assessment in timed exam conditions or being judged by coursework assignments. Essay writing skills are crucial in both instances - in fact they are essential if you want to achieve high grades.